Analysis of the Performance of the Election-Winning Agency of the Regional Representative Council of the Indonesian Democratic Party of Struggle in Aceh in Nominating Legislative Candidates for the 2024 Simultaneous General Election - Nofriadi, Nofriadi; Hasan, Effendi; Rassanjani, Saddam; Helmi, Helmi; Afrijal, Afrijal (Electronic Journal of Education, Social Economics and Technology, 2024)
This study focuses on the performance of the Electoral Victory Agency (Badan Pemenangan Pemilu, or BAPILU) of the Regional Representative Council of the Indonesian Democratic Party of Struggle (PDI-P) in Aceh Province in nominating legislative candidates for the 2024 simultaneous general elections. BAPILU PDI-P Aceh Province is tasked with recruiting legislative candidates in preparation for the 2024 elections in Aceh. The stages carried out by BAPILU in nominating legislative candidates include three main phases: screening, which involves selecting prospective legislative candidates; mapping, which entails profiling the selected candidates by examining their backgrounds and personal profiles; and finally, winning, which is the final stage of candidate selection, where BAPILU determines and approves candidates to run for legislative office based on qualifications set by the PDI-P. In preparation for the upcoming 2024 elections, PDI-P prioritizes "fighter" cadres, defined as individuals with the competence and strong public influence needed to secure legislative positions. These "fighters" are considered to increase the likelihood of electoral success significantly.